Comparative analysis of groundwater potential assessment in Dharmapuri District, Tamil Nadu, India - Prabu Babu; Saurabh Chandra Maury (Applied Water Science)
Abstract Population growth has significantly affected groundwater resources globally. Groundwater is essential for agriculture and human consumption. Considering these issues, we focused on the Dharmapuri District, Tamil Nadu, India. In the study area, 70 $$%$$ % of the population depend on agriculture, necessitating assessing groundwater potential zone. Thematic layers such as geology, geomorphology, drainage density, lineament density, slope, soil, land use and land cover, recharge, distance from river, elevation, topographic wetness index and normalized difference vegetation index have been created using ArcGIS. The study aims to assess groundwater potential zones (GWPZ) using enhanced trapezoidal fuzzy number in analytical hierarchy process (ETFAHP) and analytical hierarchy process (AHP) methods with help of ArcGIS. Thematic layer(parameters) weights are calculated using AHP and ETFAHP methods. Notably, previous studies have not used trapezoidal fuzzy numbers in GWPZ. A trapezoidal fuzzy number in AHP method is used to assess GWPZ. The groundwater potential zone is classified as very poor, poor, moderate, fair and very good. The AHP and ETFAHP on groundwater potential index (GWPI) are validated with depth to water level. In this study, AHP on GWPZ showed very poor (15.00%), poor (27.85%), moderate (26.54%), fair (19.80%) and very good (10.81%). Similarly, ETFAHP on GWPZ showed very poor (17.63%), poor (27.58%), moderate (22.77%), fair (21.48%) and very good (10.54%). The area under the curve (AUC) values for AHP and ETFAHP on groundwater potential zones are 0.88 and 0.91, respectively. The AUC value of 0.91 indicates best prediction accuracy in the study area.